2001
DOI: 10.1007/bf02707626
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of export performance: A firm-level study of Italian manufacturing

Abstract: F10, D21, O33,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 15 publications
6
54
1
5
Order By: Relevance
“…Here we report the most parsimonious specification of the Heckit model. Variables included in the export equations are also in line with previous studies on the export performance of Italian manufacturing firms (see, among others: Basile, 2001;Sterlacchini, 2001). …”
mentioning
confidence: 93%
“…Here we report the most parsimonious specification of the Heckit model. Variables included in the export equations are also in line with previous studies on the export performance of Italian manufacturing firms (see, among others: Basile, 2001;Sterlacchini, 2001). …”
mentioning
confidence: 93%
“…Ireland (Roper et al 2006), Italy (Sterlacchini 2001) and exports is confirmed in the empirical literature on both the manufacturing sector (e.g. Roper et al 2006, Wagner 2001, Wakelin 1998 Wagner 1995, Bernard & Jensen 1999.…”
Section: The Determinants Of Export Performance: Literature Surveymentioning
confidence: 69%
“…Still evidence at this micro level does not seem to be conclusive, as inconsistent results have frequently been found (e.g. Sterlacchini, 2001).…”
Section: Earlier Empirical Studiesmentioning
confidence: 88%